PENGARUH INSENTIF DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT BFI FINANCE INDONESIA TBK CABANG DEPOK - Rico Lare Alamsyah; Ibrahim Bali Pamungkas (Journal of Research and Publication Innovation, 2024)
This research aims to determine the effect of incentives and competencies on employee performance at PT. BFI Finance Indonesia Tbk Depok Branch either partially or simultaneously. The population of this research is employees of PT. BFI Finance Indonesia Tbk Depok Branch, while the sample for this research is employees of PT. BFI Finance Indonesia Tbk Depok Branch, totaling 80 people. The research method used in this research is quantitative research. The data analysis used in this research is the classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and F test. The results of this research are that incentives have a significant effect on employee performance with the Y regression equation. = 35.869 + 0.146X1, a correlation value of 0.270, meaning that the two variables have a low level of relationship. Hypothesis testing obtained a calculated t value > from t table (2.478 > 1.991). Competence has a significant effect on employee performance with the regression equation Y = 31.134 + 0.257X2, a correlation value of 0.436, meaning the two variables have a moderate level of relationship. Hypothesis testing obtained a calculated t value > from t table (4.279 > 1.991). Incentives and Competencies simultaneously have a significant effect on Employee Performance with the regression equation Y = 30.600 + 0.033X1 + 0.238X2. The coefficient of determination value is 38.1% while the remaining 61.9% is influenced by other factors. Hypothesis testing obtained F count > F table (9.199 > 2.723).